Desarrollo de la competencia metalingüística en Secundaria mediante la producción de microtextos: el concepto de cambio semántico - Allué Villanueva, Consuelo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
We consider documenting and analyzing actual examples of the classroom work, the positive answer of the students to tasks of writing that promote the development of the metalinguistic awareness, critical thinking and learning to learn competences, by means of the individual writing production put jointly in great group later. This practice demonstrates possible and necessary new learning methodologies and the change of the educational urgent paradigm in Secondary Education. We will use examples of actual texts of the students in Spanish Language and Literature, prepared for the acquisition of the concept of semantic change. In the line of research of active methodologies, competences learning and some aspects of creative writing, following the current «unstructured game», we propose this «not so structured writing» which reject the dependence of the literal reading. The most relevant results demonstrate essential and not so classical proposals of task and perspectives for the development of the metalinguistic awareness. The employment of nearby examples that draw the attention on the mechanisms of languages also turns out to be effective to stimulate thinking, reverse knowledge and uses, improve metalinguistic awareness and develop more receptive attitudes.